PERUBAHAN PANDANGAN ONTOLOGI PADA WAYANG MASA ISLAM DAN PRA ISLAM - Siswanto, Nurhadi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2017)
Puppet has developments and changes over time. Puppet continues to grow and develop in accordance with the development of the dominant civilization that accompanies it. A change in the function of puppet strikingly occurs in Islam and pre-Islamic era. Puppet that previously acted as a form of religious ritual to worship the ancestors and the ‘Dewa’ has been changes in function to serve as a media for the sake of religion propaganda and education. There was also a change on the ontological view in puppet. The changes occur due to difference concept of Deity’s thought in Islam and Hinduism. The Islam belief that does not recognize the concept ‘dewa’, it is not eliminating the existence of ‘dewa’ in various puppet stories, but instead desecrated it. ‘Dewa’ no longer considered sacred, perfect and unbeatable, but the god is considered common creatures that could also be defeated and make mistakes.